2015
DOI: 10.1159/000433543
|View full text |Cite
|
Sign up to set email alerts
|

Occult Tumor Cells in Lymph Nodes of Patients with Gastric Cancer: A Systematic Review on Their Prevalence and Predictive Role

Abstract: Background and Aims: The presence of lymph node (LN) metastasis is a key prognostic factor for gastric adenocarcinoma. However, even among patients without LN metastasis (N0), recurrence may occur. In some of these cases, occult tumor cells (OTC) are thought to play an important role. We aimed to determine the prevalence of OTC and its clinical relevance. Methods: We conducted a systematic review of studies in English published until September 2013 that addressed OTC prevalence and/or its clinical relevance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(187 reference statements)
0
6
0
Order By: Relevance
“…The higher probability of micrometastasis and ITC occurrence in diffuse gastric cancer (50,55,56) potentially supports the importance of lymph node immunostaining in this cancer type. Although lymph nodes harboring IHC-detected micrometastasis are considered positive nodes in gastric carcinoma, their clinical impact is unclear (58). Gastric cancer patients classified as N0 by routine histology turned out to bear micrometastases and/or ITC after IHC have been proposed for additional treatment after surgery (59).…”
Section: Micrometastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher probability of micrometastasis and ITC occurrence in diffuse gastric cancer (50,55,56) potentially supports the importance of lymph node immunostaining in this cancer type. Although lymph nodes harboring IHC-detected micrometastasis are considered positive nodes in gastric carcinoma, their clinical impact is unclear (58). Gastric cancer patients classified as N0 by routine histology turned out to bear micrometastases and/or ITC after IHC have been proposed for additional treatment after surgery (59).…”
Section: Micrometastasesmentioning
confidence: 99%
“…Gastric cancer patients classified as N0 by routine histology turned out to bear micrometastases and/or ITC after IHC have been proposed for additional treatment after surgery (59). Despite judging controversial the prognostic role of ITC in gastric cancer lymph nodes based on a review of literature, Tavares et al proposed this descriptor as a valid prognosticator provided proper definitions, methodology, stage groups, extension of lymphadenectomy and follow-up are used, implying a possible impact on therapy (58). SLN SLN navigation surgery, i.e., the removal of the first(s) lymph node(s) only along the lymphatic drainage from a malignancy, followed by a thorough pathological analysis, is an accepted standard treatment procedure for malignant melanoma and breast cancer.…”
Section: Micrometastasesmentioning
confidence: 99%
“…Our study also found that the prognosis of patients with >12 lymph nodes retrieved was relatively better (HR: 0.64, 95% CI: 0.56–0.72, P <0.001). New lymph node staging indicators such as metastatic lymph nodes ratio, log odds of positive lymph nodes, negative lymph node count, and lymph node micrometastasis may predict prognosis more accurately ( 52 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review regarding gastric cancer concluded that eight studies found no association, whereas 18 studies found micrometastasis was associated with a poorer prognosis. However, just six studies presented a significantly different 5‐year survival rate between patients with and without micrometastasis …”
Section: Discussionmentioning
confidence: 99%